Setup latency analysis of CAPWAP Centralized WLAN Network - Balfaqih, Mohammed; Hassan Abdalla Hashim, Aisha; Mahmoud, Omer; Mazlan, M. Hasbullah; Haseeb, Shariq; Hasnan, S. N (Journal of Telecommunications Publication, 2012)
High number of Access Points (APs) in large-scale networks have introduced several overheads such as control,management and monitoring. Distributing and maintaining a consistent configuration while considering security issues presentseven more challenges in large deployments and new architectures. These issues forced many network vendors such as Aruba,Cisco and Meraki to offer proprietary centralized solutions. Since the proposed solutions don’t provide any form ofinteroperability, Control and Provisioning of Wireless Access Point (CAPWAP) Working Group had defined standardinteroperable protocol to address the aforementioned problems. By using Access Controller (AC) and Wireless TerminationPoint (WTP), this interoperable protocol allows network operators to control their wireless network infrastructure and extendsmanageability. This paper evaluates the latency involved with setup process in three cases; normal setup process, pre-configured setup process and setup process with considering failure states. The results showed that the main latencycontributor is the Discovery phase, while the error during DTLS Establishment phase cost more time than other phases